The Drosophila ovarian tumor gene is required for the organization of actin filaments during multiple stages in oogenesis. - Rodesch, C.; Pettus, J.; Nagoshi, R.N. (Developmental Biology, 1997)
The ovarian tumor gene is required during both early and late stages of oogenesis. Mutations produce a range of phenotypes, including agametic ovarioles, tumorous egg chambers, and late stage oogenic arrest. We demonstrate that each of these phenotypes is associated with specific aberrations in actin distribution. In the earliest case, ovarian tumor mutations cause actin filaments to accumulate ectopically in the fusome. This correlates with abnormal fusome morphology and arrested germ cell development in the germaria. Similarly, ovarian tumor function is required for the localization of actin that is essential for the maturation of ring canals. This defect gives rise to tumorous egg chambers in which germ cell numbers and morphology are profoundly aberrant. We also confirm that ovarian tumor is required for the formation of the nurse cell cytoplasmic actin array that is essential for the nonspecific transport of cytoplasmic contents to the oocyte during late oogenesis. Our data suggest that at this stage ovarian tumor controls the site where actin filaments initiate. Taken together, these studies suggest that the diverse ovarian tumor mutant phenotypes derive from the mislocalization of actin filaments, indicating a role for this gene in organizing the female germline cytoskeleton, and that the misregulation of actin can have profound effects on germ cell division and differentiation.